Hukum dan Etika Deepfake Urgensi Regulasi Khusus atas Konten Manipulatif di Media Sosial dalam Konteks Demokrasi Digital - Kriswandaru, Althea Serafim; Pertiwi, Berliant (PSHPM Untag Semarang, 2025)
The proliferation of deepfake technology, powered by artificial intelligence, presents a growing threat to digital democracy by enabling the spread of highly realistic manipulated content that can distort public perception, undermine trust, and disrupt electoral integrity. This study critically examines the urgency of establishing specific legal regulations for deepfake content in Indonesia, where existing cyber laws remain too general to address the nuances of AI-generated disinformation. Employing a qualitative normative-legal approach and comparative analysis with legal frameworks in the United States, South Korea, and the European Union, the research identifies a significant regulatory gap and offers a multidimensional framework that integrates legal, ethical, and democratic perspectives. The findings reveal that Indonesia lacks a clear definition and legal category for manipulated content, resulting in insufficient legal protections for individuals and institutions vulnerable to digital deception. The study proposes a context-sensitive model of regulation that aligns with international best practices and responds to Indonesia’s legal and sociopolitical realities. This research contributes to the discourse on digital law by offering a novel regulatory scheme capable of addressing the ethical and democratic challenges posed by deepfake technology.